THE EFFECT OF MOTIVATION TOWARD EFL LEARNERS’ ENGLISH READING SKILL ACHIEVEMENT - Kawakiby, Ihza Noval; St. Shabibatul Rohmah; Rizki Nurfida Pambayun (Esteem Journal of English Education Study Programme, 2025)
This study investigates how intrinsic and extrinsic motivation affect the reading performance of third-grade EFL students at Al Kautsar Putra Secondary School. Using a qualitative approach, data were gathered from questionnaires, interviews, and academic records. The questionnaire, with "agree" or "disagree" options, assessed students’ motivation toward reading English texts. Ten randomly chosen students also participated in interviews. Findings showed that 70% were mainly influenced by extrinsic factors such as grades, rewards, and teacher expectations. However, some students demonstrated intrinsic motivation, enjoying the reading process and feeling satisfied when understanding texts independently. Interview data revealed a mix of motivations, with peer and teacher support playing key roles. Institutional support, such as structured activities and social reinforcement, was found to significantly boost motivation and reading growth. These supports also improved students’ confidence in speaking English. Consistent academic progress in reading scores from Grade 7 to Grade 9 further confirmed that motivation, supported by continuous instruction, positively impacts language learning outcomes.